2020
DOI: 10.1177/0886260520914560
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Fear of Victimization Among College Students in Spain: Gender Differences and Similarities

Abstract: Past studies that have analyzed fear of victimization using samples composed of men and women have most frequently controlled for the effect of gender. This study not only controls for the effect of gender, but also examines how the predictors of fear of victimization may vary across gender. To do so, separate regression models for men and women were estimated and the corresponding z tests were calculated for the purpose of analyzing whether the differences between genders were significant. The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…First, regardless of the daylight, girls did not feel significantly less safe compared to boys, which contrasts with the prevailing body of literature pertaining to adults (Johansson & Haandrikman, 2021;León et al, 2022;Mak & Jim, 2018;Soto et al, 2022), as well as adolescents (Johansson et al, 2009;McCray & Mora, 2011;Rišová & Sládeková Madajová, 2020). This can be explained by the underrepresentation of those threats that have been generally considered to cause the gender differences in unsafety perceptions.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…First, regardless of the daylight, girls did not feel significantly less safe compared to boys, which contrasts with the prevailing body of literature pertaining to adults (Johansson & Haandrikman, 2021;León et al, 2022;Mak & Jim, 2018;Soto et al, 2022), as well as adolescents (Johansson et al, 2009;McCray & Mora, 2011;Rišová & Sládeková Madajová, 2020). This can be explained by the underrepresentation of those threats that have been generally considered to cause the gender differences in unsafety perceptions.…”
Section: Discussionmentioning
confidence: 65%
“…Research to date has shown that gender is one of the most important unsafety perception predictors (Mak & Jim, 2018;Soto et al, 2022). In general, women and girls feel more insecure in public spaces than men and boys (Johansson & Haandrikman, 2021;León et al, 2022;McCray & Mora, 2011;Sk�r, 2010), and are considered more vulnerable by their relatives (Hatamzadeh et al, 2017;Osman & Jíchová, 2019;Vozmediano et al, 2017). As a result, such concerns may discourage women from using public spaces equally to men (Carver et al, 2010;Soltani & Zamiri, 2011;Tandogan & Ilhan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Research has found that sociodemographic factors, such as age and gender, play a significant role in shaping individual perceptions of risk (LaGrange & Ferraro, 1989;León et al, 2020;Rader et al, 2012;Schafer et al, 2006) and are associated with more frequent use of avoidance strategies to manage perceived risk (Cobbina et al, 2008;Fisher & Sloan III, 2003;Madriz, 1997). The preponderance of evidence suggests that individuals who identify as women are more likely to exhibit higher levels of FOV and avoidance behavior than those who identify as men (Carro et al, 2010;Ceccato & Loukaitou-Sideris, 2022;Killias, 2000;Smolej & Kivivuori, 2006).…”
Section: Avoidance Behaviors and Correlatesmentioning
confidence: 99%
“…As a clear sign of how sexual violence could contribute to creating a climate of fear in society, research shows that women's higher fear of crime compared with men can largely be explained by fear of rape [6]. Research shows that women express greater overall levels of fear of crime and even higher levels of fear of sexual crimes in comparison with men [7]. These results are consistent across countries and populations (college students, general population) [8] and can be explained, partly, because of the shadow of sexual assault [9].…”
Section: Introductionmentioning
confidence: 99%
“…The Perceptions of Sex Offenders Scale, PSO [23] measuring attitudes toward sex offenders. It consists of 20 items that are scored on a 7-point Likert-type scale ranging from "strongly disagree" (1) to "strongly agree" (7). It has three subscales: sentencing and management (e.g., "People who commit sex offences should lose their civil rightse.g., voting, privacy", Cronbach's α = 0.87), stereotype endorsement (e.g., "Most sex offenders do not have close friends", Cronbach's α = 0.83), and risk perception (e.g., "Only a few sex offenders are dangerous"-reverse scored, Cronbach's α = 0.70).…”
mentioning
confidence: 99%